Demonstrated cost-effectiveness of food-assisted maternal and child health and nutrition program on maternal and child nutritional outcomes in Guatemala and Burundi - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The costing study was published open access online in Maternal and Child Nutrition in June 2019. One finding suggested that extending the programs for 2 years would have saved between 11%-18% per beneficiary. Findings like these can help program implementers and funders design more effective multisectoral health and nutrition programs.